Β-catenin activation in hair follicle dermal stem cells induces ectopic hair outgrowth and skin fibrosis. (16th May 2018) - Tao, Yixin; Yang, Qingchun; Wang, Lei; Zhang, Jie; Zhu, Xuming; Sun, Qianqian; Han, Yunbin; Luo, Qian; Wang, Yushu; Guo, Xizhi; Wu, Ji; Li, Baojie; et al.
Abstract: Hair follicle dermal sheath (DS) harbors hair follicle dermal stem cells (hfDSCs), which can be recruited to replenish DS and dermal papilla (DP). Cultured DS cells can differentiate into various cell lineages in vitro . However, it is unclear how its plasticity is modulated in vivo . Wnt/β-catenin signaling plays an important role in maintaining stem cells of various lineages and is required for HF development and regeneration. Here we report that activation of β-catenin in DS generates ectopic HF outgrowth (EF) by reprogramming HF epidermal cells and DS cells themselves, and endows DS cells with hair inducing ability. Epidermal homeostasis of pre-existing HFs is disrupted. Additionally, cell-autonomous progressive skin fibrosis is prominent in dermis, where the excessive fibroblasts largely originate from DS. Gene expression analysis of purified DS cells with activated β-catenin revealed significantly increased expression of Bmp, Fgf, and Notch ligands and administration of Bmp, Fgf, or Notch signaling inhibitor attenuates EF formation. In summary, our findings advance the current knowledge of high plasticity of DS cells and provide an insight into understanding how Wnt/β-catenin signaling controls DS cell behaviors.